Teacher commitment and pedagogical content knowledge as predictors of students’ achievement in english grammar in junior secondary schools in akinyele local government, Ibadan, Oyo state, Nigeria (2024)
English grammar is an important aspect of English Language. Proficiency in it is indispensable for fluent oral and written communication. This study examines the relationship between teacher commitment and pedagogical content knowledge as predictors of students' achievement in English grammar in Akinyele local government, Ibadan, Nigeria. Using a descriptive research design, the study involved a simple random sampling of 200 students and 8 teachers from 4 secondary schools. Data were collected using the Teacher Commitment, Pedagogical Content Knowledge Rating Scale, and the English Grammar Achievement Test. The results showed low achievement in English grammar (x̄ = 8.07), despite teachers' high commitment (x̄ = 3.34) and pedagogical content knowledge (x̄ = 3.46). However, neither teacher commitment (r = -0.132, p > 0.05) nor pedagogical content knowledge (r = 0.202, p > 0.05) significantly correlated with students' grammar achievement. The findings suggest that while teachers exhibit positive attitudes and sufficient knowledge, these factors do not directly enhance student performance. The study recommends ongoing professional development for English teachers to improve their instructional strategies and foster a collaborative learning environment where they can share knowledge and best practices to enhance students' achievement in English grammar